Study on the mycoflora and the production of Ochratoxin a (OTA) by mould on Coffea robusta in Vietnam - Hong Mien, Dang Vu; Hai, Chau Ngoc; Hien, Lam Thanh; Huong, Tu Thi (Academia Journal of Biology, 2012)
103 samples of Coffea robusta were investigated, 507 fungi trains were isolated on Czapek or PDA media for identification. 52 species from 9 genera were listed. The genus Aspergillus with 25 species and Penicilium with 13 species represented respectively 43% and 23% of the total number of species. The Ochraceus group, well-known as OTA potential producers with 6 species represented 9% of the total number of isolates. By direct plating, the beans with the moisture of 11-14%, were heavily contained by moulds (80 to 100% of the beans plated) and those with the moisture of 9-10,5 % were lightly infected (10.3%). 22 species (40%) were known as producers of different mycotoxins. OTA were present on 50 of the 52 samples examined (96.4%), but the level was not high: 88.5% with less than 1 ppb/kg. The authors proposed that Vietnamese C. robusta green beans for exportation would have less than 11% moisture to prevent mould growth and in a humid tropical climate of Vietnam, to prevent dehumidification, the beans would be packed in two-coated bag, the inside coat in polyethylene sheet of 0.08 mm thick and the external one in jute as ordinary. The beans thus would be prevented from dehumidification and mould formation for at least 5 to 6 months.